SNhunt151: an explosive event inside a dense cocoon. Issue 2 (9th January 2018) - Elias-Rosa, N; Benetti, S; Cappellaro, E; Pastorello, A; Terreran, G; Morales-Garoffolo, A; Howerton, S C; Valenti, S; Kankare, E; Drake, A J; Djorgovski, S G; Tomasella, L; et al.
Abstract: SNhunt151 was initially classified as a supernova (SN) impostor (nonterminal outburst of a massive star). It exhibited a slow increase in luminosity, lasting about 450 d, followed by a major brightening that reaches MV ≈ −18 mag. No source is detected to MV ≳ −13 mag in archival images at the position of SNhunt151 before the slow rise. Low-to-mid-resolution optical spectra obtained during the pronounced brightening show very little evolution, being dominated at all times by multicomponent Balmer emission lines, a signature of interaction between the material ejected in the new outburst and the pre-existing circumstellar medium. We also analysed mid-infrared images from the Spitzer Space Telescope, detecting a source at the transient position in 2014 and 2015. Overall, SNhunt151 is spectroscopically a Type IIn SN, somewhat similar to SN 2009ip. However, there are also some differences, such as a slow pre-discovery rise, a relatively broad light-curve peak showing a longer rise time (∼50 d), and a slower decline, along with a negligible change in the temperature around the peak ( T ≤ 10 4  K). We suggest that SNhunt151 is the result of an outburst, or an SN explosion, within a dense circumstellar nebula, similar to those embedding some luminous blue variables like η Carinae and originating from past mass-loss events.